A Application of Hadith on Accounts Receivable and Its Implementation in Sharia Bank Guarantees - Irham Maulana; Nourelhuda S. B. Elmanaya; Mohamed Gamal Ibrahim ElBasiouny; Ubed Abdilah Syarif; Nuha Nuha (Demak Universal Journal of Islam and Sharia, 2023)
The purpose of this study is a reflect the phenomenon, where since the introduction of Islamic banking in 1991, the Islamic economy has grown rapidly. Various service products have been issued by Islamic banks and other financial institutions that facilitate these services by listing various fatwas of the National Sharia Council - Indonesian Ulema Council (DSN-MUI). So the question arises how is the application of the Hadith on Accounts Receivable and its Implementation on Bank Guarantees? This research method is qualitative by taking data from review literature that is compromised with field facts that take the object of research on bank guarantees. The results of the study concluded that one of the sharia banking services is the Sharia Bank Guarantee with a kafalah fatwa as its sharia legality issued by DSN MUI No: 11/DSN-MUI/IV/2000. The contract used is a kafalah bil ujrah contract, which is a guarantee transaction provided by a bank in exchange for wages, but this contract is a contract that is controversial in terms of the legality of the arguments described by DSN-MUI and the arguments of other parties who prohibit it because it resembles the qardh contract that takes the benefits of usury, which of course requires offering contract options that can be done to get out of the controversy.